PELANGGARAN MAKSIM KERJA SAMA DAN IMPLIKATUR DALAM TUTURAN SINETRON KOMEDI OK-JEK SEASON 2 EPISODE 498—500 - Najmaturrahmi, Najmaturrahmi; Patriantoro, Patriantoro; Heryana, Nanang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The maxim of cooperation is a rule that must be fulfilled by participants so that the conversation goes well. But, not all conversations follow the maxim of cooperation. In addition, the speech participants must be able to understand the intent and meaning of speech uttered by the opponent's speech. The purpose of this research was to describe the form of violations of the maxim of cooperation, implicature and implementation of Indonesian language learning in speech of sitcoms ok-jek season 2 episode 498—500. The method used in this research is descriptive method and context analysis method. The technique of collecting data used is documentary techniques, and see techniques. The tools used to collect data are stationery, laptops and data cards. Data analysis techniques use pragmatic matching techniques and referential equivalents .The results of the study were violation of the maxim of cooperation is caused by the addition of excessive information, short speeches, situations, lies, distracting speech, and convoluted sentences. The implicature that exists in every episode of the ok-jek comedy soap opera is the implicature of affirming, informing, complaining, denying, asking, and joking. Ok-jek Sitcom can be used as a reference for learning to produce anecdotal texts. Keywords: violation of maxim, implicature, sitcoms, implementation